MANAJEMEN SEKOLAH BERBASIS 5 PILAR: ISLAMIC, GREEN, LEADERSHIP, CHILDREN FRIENDLY, DAN INCLUSIVE UNTUK MENGEMBANGKAN AKHLAK ISLAMI PESERTA DIDIK - Chafid Sugianto; Griet Helena Laihad; Sutji Harijanto (Universitas Pakuan, 2020)
5 PILAR BASED SCHOOL MANAGEMENT: ISLAMIC, GREEN, LEADERSHIP, CHILDREN FRIENDLY, AND INCLUSIVE TO DEVELOP ISLAMIC MORALS OF STUDENTSThis study is intended to obtain the picture of the 5 pillars of the Kreativa Elementary School management: Islamic, Green, Leadership, Children Friendly, and Inclusive in the form of data and information in order to develop Islamic morals of the students. This research uses qualitative methods, with the researcher as an instrument. The data collection techniques used were interviews, observation, and documentation study. Based on the existing data and information, it can be concluded that the management function of planning, organizing, directing, and controlling plays an important role in achieving the school goals. School management strives to achieve the goal of developing Islamic morals for students through the application of 5 pillars: Islamic, Green, Leadership, Children Friendly, and Inclusive as the basis for educational programs at Kreativa Elementary School. To achieve these goals, it requires planning that has a strong concept to achieve goals, organizing that is tailored to the needs of the school, directing resources according to the program that has been planned and organized, and control that includes all components of the educational program.